2014
DOI: 10.2298/tsci110826089k
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermal behavior and fluid motion in DC magnetohydrodynamic pumps

Abstract: Motivated by increasingly being used magnetohydrodynamic micropumps for pumping biological and chemical specimens, this study presents a simplified magnetohydrodynamic flow model based upon steady-state, incompressible and fully developed laminar flow theory in rectangular channel to offer the characteristics of magnetohydrodynamic pumps for prediction of pumping performance in magnetohydrodynamic flow. The non-linear governing equations of motion and energy including viscous and Joule dissipation are solved n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The flow rate can be increased either by increasing applied current, keeping magnetic flux constant or by increasing magnetic flux while keeping the applied current constant to enhance the pump performance. Similar trends have been observed by previously conducted studies [16]. For low Hartmann numbers, the velocity increased with an increase in the Hartmann number.…”
Section: Magnetohydrodynamic Pump (Mhd) Performancesupporting
confidence: 91%
See 1 more Smart Citation
“…The flow rate can be increased either by increasing applied current, keeping magnetic flux constant or by increasing magnetic flux while keeping the applied current constant to enhance the pump performance. Similar trends have been observed by previously conducted studies [16]. For low Hartmann numbers, the velocity increased with an increase in the Hartmann number.…”
Section: Magnetohydrodynamic Pump (Mhd) Performancesupporting
confidence: 91%
“…The authors presented optimization of mean Nusselt number using orthogonal array optimization. Kiyasatfar et al [16] investigated thermal behavior and fluid motion in direct current (DC) MHD pump by varying magnetic flux density, applied current and channel size. The authors found that the maximum velocity increases with increase in applied current and as Hartmann number increases the velocity profile becomes flatter.…”
Section: Introductionmentioning
confidence: 99%
“…Few research studies about the MHD effect on micro-channels noticed the improvement of their hydraulic and thermal behavior. The decrease of the gradient of velocity at the wall with a rise in the index of Power-law flow was observed in the flow of non-Newtonian fluid flow in a microchannel under a transfer magnetic field [85]. The increment of the gradient of velocity near the wall and reduction of maximum velocity was found with the rising Hartmann number.…”
Section: Figure 21mentioning
confidence: 83%
“…One of them is also Attia [4] who investigated the Hall current effects on the velocity and temperature fields of an unsteady Hartmann flow. Recently, Kiyasatfar et al [5] presented investigation of thermal behavior and fluid motion in DC MHD pumps, Chandrasekhar and Sharma [6] presented heat transfer of a nanofluid in a circular duct, while Abou-Zeid [7] gives the solution for MHD non-Newtonian nanofluid flow through a porous medium in eccentric annuli.…”
Section: Introductionmentioning
confidence: 99%